Gingival crevicular fluid and serum leptin: their relationship to periodontal health and disease - B. V. Karthikeyan (Blackwell Synergy, 2007)
Background & Aims: Leptin is a pleiotrophic hormone produced by adipose tissue and it plays an important role in protection of the host from inflammation and infection. The purpose of this study is to determine the presence of leptin in gingival crevicular fluid (GCF) and serum samples and to find out their association, if any. Methods: Forty two subjects were selected based on their body mass index and were divided into three groups of 14 each; healthy (Group I), chronic gingivitis (Group II) and chronic periodontitis (Group III). GCF samples (by microcapillary pipettes) and serum samples (by venipuncture) were collected to estimate the levels of leptin using enzyme linked immunosorbent assay kit. Results: The highest mean leptin concentration in GCF was obtained for Group I (2658 pg/ml) and the least for Group III (1312 pg/ml). In contrast, the lowest serum leptin concentration was obtained for the Group I (8783 pg/ml), and the highest for Group III (12082 pg/ml). This suggests a negative correlation of GCF leptin concentration and a positive correlation of serum leptin concentration as the clinical attachment level progresses (po0.05). Conclusion: These results suggest that greater the periodontal destruction, lesser is the GCF leptin concentration and greater the serum leptin concentration.